MeerKAT’s view of radio morphologies in the nearby X-shaped and dual-AGN system NGC 326 - Rasakanya, William Tabudi (My University, 2024)
Hierarchical structure formation in the Universe naturally predicts frequent galaxy mergers, and as a result, supermassive black hole mergers. A dual-AGN phase will then occur during the course of those mergers. Constraining the timescales spent at this stage provides predictions for supermassive black hole merger event rates and constraints on galaxy formation and evolution. Supermassive black holes at the centres of their host galaxies actively accrete matter in some systems, resulting in a production of radiation in a broad wavelength range, and in a fraction of those, radio-bright jets. The relativistic jets are usually paired and can span from parsec to megaparsec scales. A subclass of those have exotic radio morphologies, including the so-called ‘X-shaped’ sources. The study of such systems is important to better understand the intrinsic and extrinsic physical properties and feedback mechanisms influencing the evolution of radio jets, as well as the identification of exotic systems which may be used as physical laboratories. In this thesis, we present MeerKAT’s first look at the prototypical, dual-AGN and previously characterised X-shaped system, NGC 326. The extended large-scale diffuse structure of NGC 326, revealed first by the LOFAR 144 MHz maps, is unveiled for the first time at GHz frequencies. Analysis of the MeerKAT L-band map, in combination with the LOFAR 144 MHz map, suggests that the production of the wings and the extended structure is a consequence of hydrodynamical backflows within the radio structure residing inside a merging cluster. Due to the high imaging fidelity, sensitivity, and dynamic range, the large-scale structure was able to be captured in the gigahertz observation, despite the low surface brightness and steep spectral index of the older plasma of the source. Detailed, multi-band imaging of nearby universe X-shaped sources such as this will directly assist in discerning the relevant physical drivers of the increasing number of exotic radio source morphologies being identified in SKA precursor and pathfinder survey
A research report submitted in partial fulfilment of the requirements for the degree Master of Science to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2023
Keywords: Hierarchical structure; Physical properties